The acute angiogenic signalling response to low-load resistance exercise with blood flow restriction. Issue 3 (16th March 2018) - Ferguson, Richard A.; Hunt, Julie E. A.; Lewis, Mark P.; Martin, Neil R. W.; Player, Darren J.; Stangier, Carolin; Taylor, Conor W.; Turner, Mark C.
Abstract: This study investigated protein kinase activation and gene expression of angiogenic factors in response to low-load resistance exercise with or without blood flow restriction (BFR). In a repeated measures cross-over design, six males performed four sets of bilateral knee extension exercise at 20% 1RM (reps per set = 30:15:15:continued to fatigue) with BFR (110 mmHg) and without (CON). Muscle biopsies were obtained from the vastus lateralis before, 2 and 4 h post-exercise. mRNA expression was determined using real-time RT–PCR. Protein phosphorylation/expression was determined using Western blot. p38MAPK phosphorylation was greater ( p  = 0.05) at 2 h following BFR (1.3 ± 0.8) compared to CON (0.4 ± 0.3). AMPK phosphorylation remained unchanged. PGC-1α mRNA expression increased at 2 h (5.9 ± 1.3 vs. 2.1 ± 0.8; p  = 0.03) and 4 h (3.2 ± 0.8 vs. 1.5 ± 0.4; p  = 0.03) following BFR exercise with no change in CON. PGC-1α protein expression did not change following either exercise. BFR exercise enhanced mRNA expression of vascular endothelial growth factor (VEGF) at 2 h (5.2 ± 2.8 vs 1.7 ± 1.1; p  = .02) and 4 h (6.8 ± 4.9 vs. 2.5 ± 2.7; p  = .01) compared to CON. mRNA expression of VEGF-R2 and hypoxia-inducible factor 1α increased following BFR exercise but only eNOS were enhanced relative to CON. Matrix metalloproteinase-9 mRNA expression was not altered in response to either exercise. Acute low-load resistance exercise with BFR provides a targeted angiogenic response potentially mediated through enhanced ischaemic and shear stress stimuli.